MODEL REGRESI LOGISTIK BINER PADA MINAT BEKERJA DI LUAR KOTA - Ningrum Fajar Wati; Ida Ayu Rachmawati Kusasih (Universitas Boyolali, 2023)
This study aims to determine the factors that influence the interest in working outside the city. Various factors include age, education level, income on interest in working outside the city. To achieve this goal, the type of data in this study is quantitative data. The data used is primary (obtained directly from the source through a questionmaire) with the analysis technique using the Binary Logistic Regression Technique because the variables are dichotomous, namely using a dummy scale. From the results of the calculation of the Slovin formula, a total sample of 99 people was obtained, but this research was conducted with 100 respondents. Data analysis was carried out using the SPSS application version 16.0 for windows. The results showed that the variables of age and income had a significant effect on interest in working outside the city, while the level of education had no significant effect on the interest in working outside the city.